2022
DOI: 10.15586/qas.v14i3.1073
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of intracellular polysaccharides from Antrodia cinnamomea on the intestinal microbiota of mice with antibiotic-associated diarrhea

Abstract: Antrodia cinnamomea is a valuable and scarce medicinal and edible mushroom. Its main active substances are triterpenoids and polysaccharides with many biological activities, such as liver protection, immunity enhancement, antitumor, anti-inflammatory, and antiviral. The long-term use of antibiotics can easily lead to disorders in the intestinal flora and causes diarrhea, inflammation, immune decline, and other symptoms. In this study, A. cinnamomea intracellular polysaccharides (AIPSs) were extracted from myce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The gut microbiota is an important microbial community in the body and plays a central role in the maintenance of health ( Zhang C. et al, 2022 ). Growing evidence has proven that disruption of the gut microbiota is characteristic of diarrhea ( Chen et al, 2019 ; Breitrück et al, 2021 ; Wu et al, 2021 ; Zhen et al, 2021 ; Chen et al, 2022 ; Lu et al, 2022 ). In our study, 16S rRNA high-throughput sequencing was used to explore whether the structure of the gut microbiota in mice with diarrhea would be altered by administration of AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota is an important microbial community in the body and plays a central role in the maintenance of health ( Zhang C. et al, 2022 ). Growing evidence has proven that disruption of the gut microbiota is characteristic of diarrhea ( Chen et al, 2019 ; Breitrück et al, 2021 ; Wu et al, 2021 ; Zhen et al, 2021 ; Chen et al, 2022 ; Lu et al, 2022 ). In our study, 16S rRNA high-throughput sequencing was used to explore whether the structure of the gut microbiota in mice with diarrhea would be altered by administration of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_NK4A136_group (belonging to the Lachnospiraceae family), a probiotic, produces short-chain fatty acids that inhibit pathogenic bacteria and are considered anti-inflammatory molecules. Multiple studies have identified decreased levels of Lachnospiraceae_NK4A136_group in the stool of mice with diarrhea, and a decrease in diarrhea symptoms is associated with increased Lachnospiraceae_NK4A136_group levels ( Breitrück et al, 2021 ; Wu et al, 2021 ; Zhen et al, 2021 ; Chen et al, 2022 ; Lu et al, 2022 ). Escherichia-Shigella are Gram-negative, and this is the main pathogen that causes diarrhea and diarrhea-related deaths ( Yan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antrodia camphorata ) is a precious edible and medicinal fungus that belongs to phylum Basidiomycetes, family Polyporaceae, and genus Antrodia [ 1 ]. A. cinnamomea presents various biological activities, such as hepatoprotective, antitumor, antioxidant, antiviral, antivasodilation, hypoglycemic, immunoregulatory, and gut microbiota regulatory [ 2 , 3 , 4 , 5 ]. The main bioactive compounds of A. cinnamomea include triterpenoids (such as antcins A, antcins B, antcins C, antcins H, antcins K, methylantcinate, and sulphurenic acid), polysaccharides, ubiquinone derivatives (such as antroquinonol, antroquinonol B, antroquinonol C, antroquinonol D, antroquinonol L, antroquinonol M, and 4-acetyantroquinonol B), maleic and succinic acid derivatives (such as antrodins A, antrodins B, antrodins C, antrodins D, and antrodins E), and benzene derivatives [ 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium difficile was first identified in a study of gut microbiota of babies about 88 years ago ( 1 ). This bacterium is a clinically significant Gram-positive, toxin-producing, spore-forming, anaerobic bacillus with a relatively large size (about 3–5 μm in length) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%